Integrated Gastronomy Travel Patterns In Kotagede Yogyakarta - Parjiati Parjiati; Syafril Syafril; Titin Titin (Universitas Pendidikan Indonesia, 2022)
Gastronomic tourism is one of the strategies in developing sustainable tourism in Kotagede, Yogyakarta. Yangko, a snack that has a unique name, is a traditional food originating from Kota Gede Yogyakarta which is currently very rare to find, even many local people do not know about the snack. This study aims to determine the concept of yangko gastronomy which includes history, philosophy, tradition, social, and to analyze how to cook traditional snacks from Kotagede, the equipment used and manufacturing standards, as well as efforts to preserve yangko. The research method used is a qualitative method, while the data collection techniques are carried out by interviews, observations, literature studies and documentation studies. The result of this research is that no one knows for sure the history of yangko in terms of name, a snack that resembles mochi cakes. Yangko is made of glutinous rice flour, tapioca, sugar, salt, water, food coloring and vanilla. Support from various parties is needed in developing yangko's business so that it can attract tourists to make yangko a gastronomic tourism destination in Kotagede Yogyakarta. The researchers describe the patterns and packages of superior gastronomic tours. Based on the study results, it was obtained that the origin name of the Yogyakarta specialty can be developed as a gastronomic tourist attraction, because it can make additional knowledge for consumers or tourists who are eating the dishes they eat. In addition, the origin name of the food can be used as a storytelling in selling Yogyakarta specialties to be used as a gastronomic tourist attraction